KUALITAS KANDUNGAN UNSUR HARA KOMPOS KOTORAN KELELAWAR DENGAN PENAMBAHAN SAMPAH ORGANIK - Nurhayati, Nurhayati; Sopiana, Sopiana; Kurniawan, Tardi; Susanto, Anto; Panduwinata, Servina (Politeknik Negeri Ketapang, 2024)
Bat feses has a potential to use as organic fertilizer. Increment organic waste like fish, fruit or vegetable can be use to increasing compost nutrient. This research aims to know the nutrient quality of bat feses compost with different organic waste increment. Bat feses analysis was doing at Chemical and Soil Fertility Laboratorium, Tanjungpura University at Pontianak. The treatments are G0 = without organic waste, G1 = bat feses + vegetable wastes, G2 = bat feses + fish wastes and G3 = bat feses + fruit wastes. The parameters observed are C-organic, N total, C/N ratio, P and K element. The data wich were carried out based on compost quality standards according to Indonesian National Standard (SNI) No. 19-7030-2004. The result showed bat feses compost with vegetable waste has lowest C-organik level is 36.61% and P element highest at 4.88%. Fish wastes showed N total highest at 7.45% and bat feses compost without organic waste increment showed K highest element at 2.07%. This meets the compost parameters is according to SNI 19-7030-2004 and all of organic wastes can be used as compost material increment on bat feses compost.